Aetiology of Epistaxis: A Retrospective Study of 87 cases at Bolan Medical Complex Hospital, Quetta (Medical Forum Monthly, 2024)
Objective: To objective of this study was to describe the aetiology of epistaxis.Study Design: Retrospective, descriptive study.Place and Duration of Study: This study was carried out at the Department of Otorhinolaryngology and Head & Neck Surgery, Bolan Medical Complex Hospital, Quetta from December 2011 to December 2013.Materials and Methods: This study included 87 patients of epistaxis of the afore-said period. Medical records of patients were reviewed retrospectively and results were analyzed.Results: The mean age of the patients was 26.70±18.10 (SD) years and male to female ratio was 2:1.Trauma (32.18%) was the commonest cause of epistaxis, followed by idiopathic group (22.99%) and hypertension (14.94%). Other causes were nasal and nasopharyngeal tumours (10.34%), inflammatory diseases of nose and sinuses (8.05%), blood dyscrasias (6.90%) and miscellaneous causes (4.60%) which included one case of aspirin induced epistaxis, one case of hereditary hemorrhagic telangiectasia, one patient of typhoid fever and one case of liver cirrhosis.Conclusion: Nasal trauma is the most common cause of epistaxis. Idiopathic group is the second in which exact cause of epistaxis is not known, followed by hypertension, while other causes are rare.